2013
DOI: 10.1021/ja404724f
|View full text |Cite
|
Sign up to set email alerts
|

A Pentacoordinate Boron-Containing π-Electron System with Cl–B–Cl Three-Center Four-Electron Bonds

Abstract: Tricoordinate boron-containing π-electron systems are an attractive class of compounds with intense fluorescence and strong electron-accepting properties. However, the impact of pentacoordination of the boron atoms on their properties has not been determined. We now disclose a B,B'-bis(1,8-dichloro-9-anthryl)-substituted 9,10-dihydro-9,10-diboraanthracene as a new pentacoordinate organoboron compound. In this skeleton, with the aid of the orthogonal arrangement of the anthryl substituent, the B and Cl atoms ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…The corresponding values for FBDT2 proved to be similar with average values of 0.015 e a 0 À3 and 0.050 e a 0 À5 . The relatively lower electron density for FBDT and FBDT2 in comparison to that reported by Yamaguchi for related B···Cl [17] and by Yamashita for B···O contacts [18] is likely a result of the smaller atomic radii and higher electronegativity of fluorine.…”
mentioning
confidence: 53%
“…The corresponding values for FBDT2 proved to be similar with average values of 0.015 e a 0 À3 and 0.050 e a 0 À5 . The relatively lower electron density for FBDT and FBDT2 in comparison to that reported by Yamaguchi for related B···Cl [17] and by Yamashita for B···O contacts [18] is likely a result of the smaller atomic radii and higher electronegativity of fluorine.…”
mentioning
confidence: 53%
“…However, degradation was observed in dilute solutions (10 –5 M) of 37 during photophysical measurements. 160 Yamaguchi and co-workers found that the introduction of two chloro atoms at the 1,8-positions of the 9-naphthalenyl substituent could stabilise the boron via Cl–B interactions. This results in a weak Cl–B–Cl three-centre, four-electron bond and a nominally five-coordinate boron centre.…”
Section: Boron-containing Polycyclic π-Systemsmentioning
confidence: 99%
“…17 Previously, Yamaguchi and co-workers demonstrated the presence of 3c-4e bonding between boron and two proximal chlorines at comparable (2.727(4) Å) B-Cl distances in a neutral triarylborane, albeit in a significantly more linear Cl-B-Cl arrangement than that found in 2 (167.2° versus 128.0° in 2). 18 Inspection of the calculations (M06-2X/6-311G(d,p) PCM CH 2 Cl 2 ) on 2 revealed that the HOMO-8 contains a degree of bonding overlap between the ortho chlorines on Cl 2 Py and boron. However, the major bonding component in this orbital is from B-Cl π donation (Figure 1, bottom left).…”
Section: -C 5 H 3 N)bcl 2 ][Al 2 CL 7 ]mentioning
confidence: 99%